PDCT-04. PHASE 1 TRIAL OF WEE1 KINASE INHIBITOR AZD1775 COMBINED WITH RADIATION THERAPY FOR CHILDREN WITH NEWLY DIAGNOSED DIFFUSE INTRINSIC PONTINE GLIOMA: A REPORT FROM THE CHILDREN'S ONCOLOGY GROUP PHASE 1 PILOT CONSORTIUM (ADVL1217). (5th November 2018) - Mueller, Sabine; Yang, Xiaodong; Pal, Sharmistha; Ermioian, Ralph; Fox, Elizabeth; Gajjar, Amar; Minard, Charles; Liu, Xiaowei; Prem, Komal; Reid, Joel; Weigel, Brenda; Haas-Kogan, Daphne
Abstract: OBJECTIVES: Children with diffuse intrinsic pontine glioma (DIPG) continue to have a dismal outcome and median survival remains stagnant at 9 months for decades. AZD1775 is an orally available inhibitor of Wee1 kinase, a key G2-M checkpoint regulator that has been shown to cross the blood brain barrier and has demonstrated efficacy in preclinical DIPG studies. METHODS: AZD1775 was administered orally in newly diagnosed children with DIPG, only on days of radiation therapy. The protocol assessed 6 dose levels starting from 50 mg/m 2 /dose and escalated up to 200mg/m 2 /dose. Dose escalation occurred first by the number of days on which AZD1775 was administered and then by an increase of the actual dose. The entire length of radiation therapy constituted the dose limiting toxicity period. Correlative studies included pharmacokinetic (PK) analyses as well as determination of expression of p-CDC2, p-HH3 and g-H2AX in peripheral blood mononuclear cells (PBMC). In the late breaking abstract we will present results of this phase 1 study including PK analyses as well as results of the correlative studies. Results of this study will lay the groundwork for subsequent clinical trials using AZD1775 in pediatric brain tumors.